Fengslende sosiologi Makt, straff og identitet i Trondheims fengsler - Rye, Johan Fredrik (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"Prison has always been an attractive object for study in the field of sociology. Few other areas of modern society demonstrate social reality's fundamental ideas so clearly and obviously than prison. Social deviance and stigma, ostracism and integration, control and discipline, power and inequality are all examples of key sociological concepts that are crystalized in daily life in a prison environment. Fengslende sosiologi. Makt, straff og identitet i Trondheims fengsler (Captivating Sociology. Power, Punishment and Identity in Trondheim's Prisons) presents twelve scholarly, peer-reviewed chapters that explore various aspects of prison as a social phenomenon, both as a part of and an expression of society. The majority of the contributions build on empirical studies at maximum and minimum-security prisons in Trondheim, but the analyses have a broader relevance - both empirically and theoretically - for our understanding of power, punishment and identity in Norwegian penal institutions. Most of the contributors are associated with the Department of Sociology and Political Science at NTNU, the Norwegian University of Science and Technology, and the department's project 'Fengslende sosiologi' ('Captivating Sociology'). Several of the texts are by former master's students in sociology and present further analyses based on their master's projects. This anthology will be of interest to scholars and practitioners in the field as well as students and others interested in prison as a social institution and penal institutions in general."